2020
DOI: 10.1016/j.ijid.2020.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for bacteremia in patients with Staphylococcus aureus bacteriuria: A retrospective cohort study

Abstract: Objectives: Staphylococcus aureus bacteriuria (SABU) is rare but can be an indicator of S. aureus bacteremia (SAB). The objective of this study was to assess the proportion of SAB in patients with SABU and identify risk factors in a hospital-based population. Methods: We used electronic databases to identify eligible patients to be enrolled in a retrospective cohort study. Inclusion criteria were (i) SABU, (ii) !18 years of age, and (iii) !1 blood culture sampled AE3 months of SABU. Patients with missing value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Many microbiology laboratories consider bacteriuria only above a minimum CFU, although a low concentration of S. aureus in urine samples may also be clinically relevant [ 5 ]. We define SABU as “the detection of S. aureus in a urine sample in any concentration (CFU/mL), independent of co-detected pathogens” [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Many microbiology laboratories consider bacteriuria only above a minimum CFU, although a low concentration of S. aureus in urine samples may also be clinically relevant [ 5 ]. We define SABU as “the detection of S. aureus in a urine sample in any concentration (CFU/mL), independent of co-detected pathogens” [ 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…The pooled prevalence of concomitant SABU in all SAB cases from eligible studies is 13%. We conducted a retrospective study (2012–2019) at the University Hospital Münster, Germany, among hospitalized patients with SABU and observed that 26.9% had concurrent or subsequent SAB [ 6 ]. Rates in other studies ( Table 2 ) range from 6.9% to 17.2% [ 15–21 ].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“… 2 , 6 , 7 It is postulated that SAB may be a cause or consequence of SABU, with risk factors for concurrent SAB including male sex, inpatient status, indicators of systemic infection, urinary tract abnormalities, lack of symptoms of urinary tract infection (UTI) and diabetes. 2 , 3 , 8 , 9 However, there is a paucity of guidance on the investigation and management of SABU, 10 including optimum antibiotic treatment.…”
Section: Introductionmentioning
confidence: 99%